The bioenergy potential of conservation areas and roadsides for biogas in an urbanized region. (15th September 2015) - Van Meerbeek, Koenraad; Ottoy, Sam; De Meyer, Annelies; Van Schaeybroeck, Tom; Van Orshoven, Jos; Muys, Bart; Hermy, Martin
Highlights: We assessed the bioenergy potential of conservation areas and roadsides in Flanders. An area of 31, 055 ha produces 203 kton DM of herbaceous biomass annually. The associated biomass supply chain was optimized with OPTIMASS in four scenarios. The net energy balance of the studied systems was 7 GJ ha −1 in the 2020 scenarios. We show that this biomass can play a role to meet the increased biomass demand in 2020. Abstract: In many urbanized areas the roadside and nature conservation management offers a biomass-for-bioenergy resource potential which is barely valorized, because of the fragmented biomass production sites and the scarcity of accurate data on the spatial availability of the biomass. In this study, a GIS based assessment was performed to determine the regional non-woody biomass-for-bioenergy potential for biogas from conservation areas and roadsides in Flanders, Belgium. These systems, with an area of 31, 055 ha, have an annual herbaceous biomass production of 203 kton dry matter. The full associated biomass-to-bioenergy supply chain was optimized in four scenarios to maximize the net energy output and the profit. The scenario analysis was performed with OPTIMASS, a recently developed GIS based strategic decision support system. The analysis showed that the energetic valorization of conservation and roadside biomass through anaerobic digestion had a positive net energy balance, although there is still much room for improvements. Economically, however, it is a less interesting biomass resource. Most likely, the economic picture would change when other ecosystem services delivered by the protected biodiversity would be taken into account. Future technical advances and governmental incentives, like green energy certificates, will be necessary to incorporate the biomass into the energy chain. By tackling the existing barriers and providing a detailed methodology for biomass potential assessments, this study tries to facilitate the valorization of conservation and roadside biomass in order to reconcile biodiversity and road safety goals with renewable energy targets.